ANALISIS FIQH SIYASAH TERHADAP KONSEP PEMERINTAHAN ISLAM MENURUT PEMIKIRAN HASAN AL-BANNA - Ahsandy Rizky Fadhlansyah; Rahman, Budiarti A.; Larissa, Dea (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
Hasan Al-Banna as the founder of the Muslim Brotherhood put forward the concept of government to harmonize religion and state. This study aims to determine Hasan al-Banna's pattern of thought in the concept of Islamic government and also to determine the relevance of Hasan al-Banna's government to the government in Indonesia. The problem in this study is how Hasan Al-Banna's pattern of thought is towards the concept of Islamic government and how is the relevance of Hasan Al-Banna's Islamic government to government in Indonesia. This study uses library research, and the nature of this research is descriptive-analysis. The data that has been collected is then analyzed using qualitative inductive analysis. The results of this study indicate that fiqh siyasa in this case addresses Hasan Al-Banna's concept of Islamic government in line with the principles of government according to Fiqh Siyasa because Islamic government is a government that is upright on Islamic law originating from the Qur'an and Sunnah. Then the relevance of Hasan Al Banna's Islamic government to government in Indonesia is that the Islamic government system in Indonesia is increasingly finding its vitality because the construction of the government system that has been implemented so far, seems to have failed to build a harmonious and humanist state order.